INKONSISTENSI HUKUM PENGATURAN PENGEMBALIAN UANG HASIL KORUPSI DARI PERSPEKTIF KEPASTIAN HUKUM - Qadri, Rahmat Tul; Kadaryanto, Bagio; Winstar, Yelia Nathassa (Collegium Studiosum Journal, 2025)
From the perspective of legal certainty, inconsistency in the regulation of the return of corruption proceeds can create uncertainty in the implementation of the law and the legal process in general. Inconsistency or inconsistency between these three regulations can create confusion in the legal process related to the return of corruption proceeds. Legal certainty is an important principle in the legal system that demands consistency and clarity in the applicable regulations. Therefore, there needs to be an effort to formulate more consistent and comprehensive regulations regarding the return of corruption proceeds to ensure better legal certainty. The purpose of this study is to analyze the legal inconsistency of the regulation of the return of corruption proceeds from the perspective of legal certainty and to analyze the legal consequences of the inconsistency of the regulation of the return of corruption proceeds from the perspective of legal certainty. The method used is normative legal research. Based on the results of the study, it is known that the Inconsistency of the Law on the Return of Corruption Proceeds from the Perspective of Legal Certainty is that the Indonesian legal system is weak in guaranteeing legal certainty. Multi-interpretable legal provisions, the absence of standard asset return mechanisms, and inconsistent judicial practices create confusion in implementation.